Alienation Among Professional Engineers: A Canadian-American Comparison - Baba, Vishwanath; Barth, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
The purpose of the study is to empirically verify the Marxian proposition that increased (decreased) control and decreased (in-creased) professional incentives bear a positive (negative) relation to alienation; and to look for possible differences between Canadian and American engineers with regard to the relationship between alienation and control-incentive structure.